2015
DOI: 10.1074/jbc.m114.634568
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hematopoietic Stem Cells Contribute to Sexually Dimorphic Inflammatory Responses to High Fat Diet-induced Obesity

Abstract: Background: Diet-induced obesity leads to a chronic low grade inflammation with production of activated macrophages associated with systemic sexually dimorphic metabolic dysfunction. Results: Males have enhanced myelopoiesis and a proinflammatory response to obesity compared with females. Conclusion: Sex differences in myelopoiesis result in dimorphic responses to obesity-induced inflammation. Significance: Given differences in inflammatory responses, targeted treatment strategies are probably required for mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
124
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(143 citation statements)
references
References 43 publications
13
124
6
Order By: Relevance
“…We found that while females had normal myeloid progenitors at baseline, these cells did not expand with HFD as we saw in males. Examining the bone marrow ex vivo, we found that female BM produced less granulocyte and macrophage colonies than males after palmitic acid (saturated fatty acid) stimulation and produced lower cytokine responses to lipopolysaccharides (LPS) (47). Fig.…”
Section: Sexually Dimorphic Macrophage Responses To High-fat Dietmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that while females had normal myeloid progenitors at baseline, these cells did not expand with HFD as we saw in males. Examining the bone marrow ex vivo, we found that female BM produced less granulocyte and macrophage colonies than males after palmitic acid (saturated fatty acid) stimulation and produced lower cytokine responses to lipopolysaccharides (LPS) (47). Fig.…”
Section: Sexually Dimorphic Macrophage Responses To High-fat Dietmentioning
confidence: 99%
“…This suggests that there is a cell-intrinsic difference in hematopoietic responses to obesity between the sexes. It may also indicate that there is a permanent, lifelong change within the HSC progenitor population after exposure to a HFD (47).…”
Section: Sexually Dimorphic Macrophage Responses To High-fat Dietmentioning
confidence: 99%
See 3 more Smart Citations